Dental amalgam: What is the future? Must we continue teaching amalgam? - Gonçalves, Sergio Eduardo de Paiva; Anauate Netto, Camillo; Navarro, Maria Fidela de Lima; Rodrigues Filho, Leonardo Eloy; Turbino, Míriam Lacalle (Brazilian Dental Science, 2015)
.